The A to Z of New Age movements - York, Michael, 1939-; York, Michael, 1939- (Lanham, Md. : Scarecrow Press, 2009)
The A to Z of New Age Movements furnishes profiles and explanations of New Age spokespeople and leaders, of a range of human potential and self-help practices, of countercultural spiritual developments, and of different groups and organizations that identify as New Age. --from publisher description
Acknowledgments -- Editor's foreword / Jon Woronoff -- Preface -- Chronology -- Introduction -- The dictionary -- Bibliography -- Index -- About the author.
Originally published as: Historical dictionary of New Age movements: Lanham, Md. : Scarecrow Press, 2004.
Includes bibliographical references (p. 209-213) and index.
Description based on print version record.
Keywords: New Age movement -- Dictionaries; RELIGION / Islam / General; Electronic books